High levels of fatty acid-binding protein 5 excessively enhances fatty acid synthesis and proliferation of granulosa cells in polycystic ovary syndrome - Jingyu Liu; Jie Li; Xin Wu; Mei Zhang; Guijun Yan; Haixiang Sun; Dong Li (BMC, 2024)
Abstract Background Polycystic ovary syndrome (PCOS) is one of the most complex endocrine disorders in women of reproductive age. Abnormal proliferation of granulosa cells (GCs) is an important cause of PCOS. This study aimed to explore the role of fatty acid-binding protein 5 (FABP5) in granulosa cell (GC) proliferation in polycystic ovary syndrome (PCOS) patients. Methods The FABP5 gene, which is related to lipid metabolism, was identified through data analysis of the gene expression profiles of GSE138518 from the Gene Expression Omnibus (GEO) database. The expression levels of FABP5 were measured by quantitative real-time PCR (qRT‒PCR) and western blotting. Cell proliferation was evaluated with a cell counting kit-8 (CCK-8) assay. Western blotting was used to assess the expression of the proliferation marker PCNA, and immunofluorescence microscopy was used to detect Ki67 expression. Moreover, lipid droplet formation was detected with Nile red staining, and qRT‒PCR was used to analyze fatty acid storage-related gene expression. Results We found that FABP5 was upregulated in ovarian GCs obtained from PCOS patients and PCOS mice. FABP5 knockdown suppressed lipid droplet formation and proliferation in a human granulosa-like tumor cell line (KGN), whereas FABP5 overexpression significantly enhanced lipid droplet formation and KGN cell proliferation. Moreover, we determined that FABP5 knockdown inhibited PI3K-AKT signaling by suppressing AKT phosphorylation and that FABP5 overexpression activated PI3K-AKT signaling by facilitating AKT phosphorylation. Finally, we used the PI3K-AKT signaling pathway inhibitor LY294002 and found that the facilitation of KGN cell proliferation and lipid droplet formation induced by FABP5 overexpression was inhibited. In contrast, the PI3K-AKT signaling pathway agonist SC79 significantly rescued the suppression of KGN cell proliferation and lipid droplet formation caused by FABP5 knockdown. Conclusions FABP5 promotes active fatty acid synthesis and excessive proliferation of GCs by activating PI3K-AKT signaling, suggesting that abnormally high expression of FABP5 in GCs may be a novel biomarker or a research target for PCOS treatment.